FAKTOR PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PERUSAHAAN JAKARTA ISLAMIC INDEX (JII) - Salsabila, Nadiah Ayu; Miranti, Titis (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Jakarta Islamic Index is a stock index in the IDX that can use as an alternative In Islamic investment. In choosing an investment object in Islamic stocks, it necessary to pay attention to the financial ratios and stock prices of companies. The purpose of this study was to determine the effect of financial ratios on stock prices on companies listed on the Jakarta Islamic Index (JII). The type of this research is quantitative. The population of 56 companies registered on the Jakarta Islamic Index (JII) for the 2012-2018 period with a sample of 11 companies. The analysis model use panel data regression using Eviews software. The type of data uses secondary data accessed through the Indonesia Stock Exchange (IDX) website. The results showed that earning per share variable has a significant effect on stock prices. While the current ratio, debt to equity ratio, total assets turnover and net profit margin variables have no significant impact on stock prices. Simultaneously variables of current ratio, debt to equity ratio, total assets turnover, net profit margin and earning per share have significant effects on stock prices. The contribution of this research can use as a reference for companies to pay attention to financial ratios that affect stock prices.